RESEARCH EMERGENCY TRANSIENTS IN POWER SYSTEMS 6 - 10 KV WITH THE THYRISTOR SWITCHES - Yuri Dyomin; Oleg Kirkorov (Вестник Северо-Кавказского федерального университета, 2022)
The conditions and the algorithms of thyristor switches to improve the reliability of power supply system 6 - 10 kV (SES) in emergency conditions: when power interruptions and short circuits (a short circuit). The most promising circuitfor the thyristor switches in the composition of one - and two-piece SES. It is non-contact switchgear (BRU), thyristor shorting (TOU) and thyristor automatic transfer switch (ATS). The results of the elements of the numerical experiment, obtained with CAD program - SES computer, developed at the NCFU. Conclusions about the permissibility of the use of thyristor switches to improve the reliability of power supply in normal and emergency modes.